Coloniality / Decoloniality of the Peruvian university - Germaná, César (2018)
This text seeks to open up some issues that will allow accounting for the deep changes that are taking place in the Peruvian university that is going through a structural crisis. When I refer to the crisis of the university, I do not mention the difficulties that are within the university system, which are many. These are shallow crises and can be resolved through some reforms. The real crisis is caused by problems that cannot be solved within the framework of the existing system, but requires another system to solve them. Higher education in Peru is in this situation. The pervasive university model in much of the twentieth century has reached a point of bifurcation. That model has eroded and we are in a chaotic period of transit towards another form of institutional organization of the production and transmission of highly qualified knowledge. The crisis of the modern / colonial university began at the end of the 60´s, and reveals its inability to solve three major complex problems: epistemological problems, institutional problems and problems of legitimacy. The interest of this work is to examine some aspects of the options opening up to the current crisis of the university institution.